KONVERSI LAHAN SAWAH DI SUBAK PETANGAN KECAMATAN DENPASAR UTARA - Wiraraja, I Gusti Jaya; Antara, Made -; Sri Astiti, Ni Wayan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 7 No 1 (2019): MEI 2019DO - 10.24843/JMA.2019.v07.i01.p3, 2019)
ABSTRACT Agricultural land has an important role as a medium to increase the income, standard of living, and welfare of farmers within. This study aims to 1) analyze the factors that influence the motivation of farmers in converting paddy fields, 2) analyze the social and economic impacts of land conversion in Subak Petangan, North Denpasar District. This research was carried out in the Subak Petangan Denpasar Utara which was chosen using  census with a population of 40 farm owner. The main instruments used in the data collection is questionnaires. Data analysis techniques used are factor analysis method and quantitative qualitative analysis. The study showed that land conversion are affected by internal and external factors. Internal factors are formed by the number of family member, level of education, life necessities (Maslow's hierarchy of needs), income from agricultural product. External factors are formed by lifestyle indicators, interest of the younger generation for farming, access to land management, availability of water irrigation. The sosial impact of land conversion are hampered on irrigation channels, the emergence of conflicts between farmers and owners of settlements, deterioration of cultural values in Subak Petangan, North Denpasar District and the economy impact are decreases in food source. All parties including the government as well as the subak member should be able to control and develop program or regulation to repress the land conversion's rate. Sosialy and economically, land conversion in Subak Petangan generate bad impact on the environment and culture around Subak Petangan rice field area.